2023
DOI: 10.1038/s41598-023-39047-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delivery time factor on treatment time and plan quality in tomotherapy

Takayuki Yagihashi,
Tatsuya Inoue,
Shintaro Shiba
et al.

Abstract: Delivery time factor (DTF) is a new parameter introduced by the RayStation treatment planning system for tomotherapy treatment planning. This study investigated the effects of this factor on various tomotherapy plans. Twenty-five patients with cancer (head and neck, 6; lung, 9; prostate, 10) were enrolled in this study. Helical tomotherapy plans with a field width of 2.5 cm, pitch of 0.287, and DTF of 2.0 were created. All the initial plans were recalculated by changing the DTF parameter from 1.0 to 3.0 in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although the A-TOMO plan improved work efficiency, the treatment delivery time was longer compared to M-TOMO plans. This could be due to several reasons, including more stringent dose constraints and the DTF parameter in A-TOMO plans being set to 1.7, which made the execution time of each rotation approximately 20 s. A previous study indicated that increasing the DTF, while improving plan quality, also led to longer dose delivery times [ 37 ]. However, this did not increase the modulation of the A-TOMO plan.…”
Section: Discussionmentioning
confidence: 99%
“…Although the A-TOMO plan improved work efficiency, the treatment delivery time was longer compared to M-TOMO plans. This could be due to several reasons, including more stringent dose constraints and the DTF parameter in A-TOMO plans being set to 1.7, which made the execution time of each rotation approximately 20 s. A previous study indicated that increasing the DTF, while improving plan quality, also led to longer dose delivery times [ 37 ]. However, this did not increase the modulation of the A-TOMO plan.…”
Section: Discussionmentioning
confidence: 99%
“…The PTV plans were optimized using the same prescription as the robust plans; however, the target was the PTV. The calculation parameters were as follows: a 2.5-cm field width, 0.287 pitch, 1.8 delivery time factor (16), and collapsed cone convolution algorithm with a 2-mm dose grid size. Treatment planning details, such as dose optimization parameters, were as described previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there have been limited studies reporting on the performance of sCTs for H&N RT plans, which tend to be very highly modulated. 13 , 33 , 34 , 35 Characterizing the effect of voxel misassignments in highly modulated treatment plans developed on sCT could allow for the development of QA criteria for the clinical implementation of H&N MRI‐only radiotherapy.…”
Section: Introductionmentioning
confidence: 99%